297 IDENTIFICATION OF NOVEL ALTERED PEPTIDE LIGANDS RECOGNIZED BY HUMAN TUMOR-REACTIVE T CELLS. (1st January 2006) - Fallahi, A.; Li, Y.; Pinilla, C.; Yee, C.
Abstract : Background: Immunotherapy offers many potential advantages to traditional chemotherapy, including high specificity and low toxicity. One of the goals of immunotherapy is to generate tumor-specific cytotoxic lymphocytes (CTLs), which have the potential to specifically kill tumors. Tumor antigens have been used to elicit CTL responses. One disadvantage of using tumor antigens is that the CTLs that recognize these antigens are often of low affinity and/or low frequency. T cell epitopes can be engineered to enhance the expansion of tumor-specific CTLs. The challenge has been to identify such altered peptide ligands (APLs). Study Design and Methods: We use a positional scanning synthetic combinatorial peptide library (PS-SCL) to identify superagonist peptides of NY-ESO-1, a tumor-associated antigen expressed in melanoma, ovarian cancer, and other solid tumors. This exhaustive search method looks at all amino acid combinations of 9mer peptides (approx. 20 9 peptides) in a positional scanning format. T cell killing of antigen-presenting cells loaded with the library was determined by chromium release assay. Biometric analysis of the data was used to identify candidate peptide sequences. These specific peptides were then tested and compared to the parental peptide NY-ESO-1 for enhanced target sensitization to lysis and capacity to elicit CTL responses in vitro. Results: Four well-characterized high affinity NY-ESO-1-specific CTL clones were used to probe the combinatorial peptide library. Potential superagonist peptides for NY-ESO-1 were identified, ranked using a scoring algorithm, and then individually tested. We identified a novel core consensus sequence within the parental epitope that yielded enhanced CTL activity. Conclusion: Through these methods we have identified several novel superagonist ligands for T cell-based immunotherapy using NY-ESO-1-specific clones. Such peptides may show promise for both adoptive therapy and cancer vaccines.